In vitro antimicrobial activity of hexane and ethanol extracts of zeyheria tuberculosa leaves - Ramos, Robson da Silva; Sarmento, Patrícia de Albuquerque; Lins, Thaís Honório; Lúcio, Ingrid Martins Leite; Conserva, Lucia Maria; Bastos, Maria Lysete de Assis (Rev Rene, 2012)
We analyzed the in vitro antimicrobial activity of ethanol and hexane extracts of Zeyheria tuberculosa leaves, known as ipê-felpudo, against several strains of pathogenic microorganisms. An in vitro experimental study was conducted in the Wound Healing Research Lab of the Nursing Course of Federal University of Alagoas, Brazil, from May to October 2011. The extracts evaluated by both the disk diffusion method and by microdilution have shown promising for Staphylococcus aureus, however for other bacterial and fungal strains there was no inhibitory activity. The tests were performed in triplicate. The results showed that both the ethanol and hexane extract showed a strong antimicrobial activity, inhibiting the strain at concentrations greater than the gentamicin, reference standard used. Antifungal activity was not observed with the extracts. It is concluded that the good antibacterial activity of these leaves and stems of this plant species is promising for further studies in animal models.